Gaya Komunikasi Kesehatan Untuk Penyembuhan Depresi Akibat Perundungan: (Analisis Semiotika Roland Barthes Pada Video YouTube @aymanalatas) - Ramdani, Taufik; Maulida, Sindi Dewanti; Rahman, Mufti Fauzi; Ameliana, Latifa; Wahidah, Alisya Fitriya Nur; Saputra, Deni (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
In the current era, information can be easily spread widely, this is due to advances in information technology, namely new media. This study analyzes the communication style in accordance with the Communicator Style Measure (CSM) theory, on a a doctor in a YouTube video that discusses bullying and depression. The method used is Roland Barthes' semiotic analysis, which is a method to find out the denotative and connotative signs in a video show. The purpose of this study is to find out the communication style used by a doctor in a video that educates about depression caused by bullying. The results indicate that at the denotation level, bullying is not only physical violence but also verbal, such as teasing that is often taken as a joke. At the connotation level, the term "bullying" reflects domination, social power, and emotional trauma. The doctor adopts a relaxed, informal and expressive communication style to connect with the audience, especially teenagers. The video also exposes the myth that verbal bullying is not serious and that mental health education can only be done by professionals such as psychologists or psychiatrists. With a casual and inclusive approach, doctors are able to deliver educational messages effectively, while challenging the stigma associated with bullying and mental health in society. This research emphasizes the importance of social media as a relevant and adaptive health education tool in the digital age